The effectiveness of problem-based learning models using a steam approach to improve students' mathematical modeling ability on static electricity materials - Hardiana, Helsi; Sitompul, Stepanus Sahala; Hamdani, Hamdani (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This study aims to determine the effectiveness of the PBL model with the STEAM approach to improving students' mathematical modeling ability (MMA) on static electricity material at SMP Negeri 2 Pontianak. This form of research is a pre-experimental design type one-group pretest-posttest design. The research sample was class IXB students at SMP Negeri 2 Pontianak (32 people), with a cluster random sampling technique. The instruments used are tests and questionnaires. Based on the results of the Wilcoxon Test, Asymp values. Sig (2-tailed) of 0.000 (z< 0.05) shows that there are differences in the mathematical modeling ability of students in the pretest and posttest, with the level of effectiveness being in the very high category (d = 5.49). Based on response questionnaire data, 97% of students responded well to treatment, and 3% were in a suitable category. The study's conclusion is applying the PBL model with a practical STEAM approach to improving the mathematical modeling ability of students on static electricity material at SMP Negeri 2 Pontianak.